A new record of Gobius jarosi (Teleostei, Gobiidae) from the Early Miocene of Poland with inference to paleogeography and palaeoecology of the Carpathian Basin. (26th November 2019) - Kovalchuk, Oleksandr; Świdnicka, Ewa; Stefaniak, Krzysztof
Abstract: Gobies (family Gobiidae) were in the past and now important components of marine ecosystems as an essential part of the food chain. However, the early fossil record of this group is relatively meager, with only scarce skeletal remains. The oldest known representative of the genus Gobius has been recently described from the Early Miocene of Czech Republic as Gobius jarosi Přikryl & Reichenbacher, 2018. Here we present a detailed study of a well-preserved goby skeleton of the same age from the Harta locality (Poland). This specimen is assumed as belonging to Gobius jarosi based on its almost complete morphological and meristic identity with the type material from the Vážany nad Litavou locality. Some aspects of the paleogeography and paleoecology of the Early Miocene fish assemblage from Harta with special reference to the Carpathian Basin are also discussed in this paper.